An observational study investigating the effect of platelet function on outcome after colorectal surgery. (May 2015) - Keeler, Barrie D.; Simpson, J. Alastair; Fox, Susan C.; Stavrou, Christiana L.; Briggs, Rebecca A.; Patel, Priya; Heptinstall, Stanley; Acheson, Austin G.
Abstract: Introduction: Previous studies have assumed patients have uniform responses to aspirin, yet significant numbers are occult hypo- or hyper- responders. A new validated test of platelet function measures platelet P-selectin expression, which rises with increased platelet activity. This study investigated the measured perioperative changes in platelet function in response to aspirin, and subsequently whether quantitative variations in platelet activity affected perioperative complication severity and frequency. Methods: 107 patients undergoing major colorectal surgery were recruited and assigned to either control (no antiplatelet therapy) or aspirin groups. P-selectin was measured following platelet stimulation at recruitment prior to cessation of medication, and at surgery before intervention. Perioperative complications, hemoglobin changes and blood transfusions were also recorded. Results: Platelet function was higher in control ( n  = 87) than aspirin group ( n  = 20) at recruitment (median 1303u [IQR 1102–1499] vs 77u [IQR 63.5–113.5], P  < 0.01) and surgery (median 1224u [IQR 944–1496] vs 281.5u [IQR 106.8–943], P  < 0.01). There was a positive correlation between length of aspirin cessation and platelet function at surgery ( R S  = 0.66, P  < 0.01). Complication rates and hemorrhagic complication rates ( P  < 0.05) were higher with aspirin than control, although complication severity was not increased. Platelet function of the entire cohort at surgery was not associated with complication rate, severity or transfusion use. Discussion: Although complication rates were higher in aspirin group, impaired platelet function within ranges seen with aspirin continuation did not affect complication severity or rate or blood transfusion use. Consequently, aspirin continuation may not affect clinical outcome in patients undergoing major colorectal surgery and requires further investigation with a large randomized trial. Highlights: Hypo- and hyper- response to aspirin are recognized phenomena. This is frequently overlooked in studies reviewing perioperative aspirin use. This study measured platelet activity in patients undergoing colorectal surgery. Cessation of aspirin for less than 7 days was insufficient to normalize activity. However, impaired activity did not affect complications or blood transfusion use.